Curricular references of physical education teachers: influence of seniority - Lenzen, Benoît; Poussin, Bernard; Dénervaud, Hervé; Cordoba, Adrián (Swiss Journal of Educational Research, 2018)
Curriculum construction in physical education (PE) is under influence of many variables whose effects are not yet well known. Questionnaire data obtained from all PE teachers of Geneva indicate that these ones stand back from official curriculum and from some potential curricular references (teacher training programme, professional journals, Internet) throughout their career. Such distantiation is discussed regarding contributions of sociology of education and sociology of organizations.